New 16th century Lithuanian compound names with stems of hypocoristic origin - Sinkevičiūtė, Daiva (Baltistica, 2022)
Compound names whose stems arose from hypocoristics constitute asubtype of Lithuanian names. Research of historical sources has revealed some newsuch names: Bučvilà, Bùgvydas (or Bgvydas), Bùtkvilas, Daũdvilas, Daũnepras,Daũtvilas, Eĩtgilas, Geĩtmantas, Kančeigãlas (or Kančeigáila), Nórgvilas, Tatavydas,Vaĩstvilas. It has also been shown that components originating in hypocoristics arefound in the already known Daũdgėlas, Geĩtkantas, Geĩtvydas, Gibutkis. Thesenames show that the inventory of proper names was expanded with parts of othernames and that names originating in hypocoristics influenced compound names. Thenew stems buč-, bug- (or būg-), butk-, daud-, daut-, eit-, geit-, kanč-, nepr-, norg-,vaist- can be added to the already known buk-, darg-, eid-, eig-, jog-, jos-, tart-. Thebase of such stems originated in the first component of a compound name and thebeginning of the second component, extended with a suffix. Except for darg- andvaist-, the stems are only found in Lithuanian names, which implies that they werecreated apart from Prussian.
Keywords: anthroponymy; Lithuanian names; compound names; hypocoristics